De kerk van de Allerheiligste Drieëenheid in Oldenzaal. bekroning op het omvangrijke oeuvre van architect Wolter te Riele (Bulletin KNOB, 2008)
Wolter te Riele Gzn. was born in Deventer on 8 September 1867. He was the son of the architect - initially carpenter - Gerhardus te Riele Wzn. (1833-1911). The Te Rieles descended from a family of Deventer carpenters. Wolter received his training at his father's, with whom he collaborated until 1902 at the St Lucas school in Gent, Belgium (1886-1889) and at the famous church builder's P.J.H. Cuypers (1889).In the early 20th century he established himself as an independent architect in Deventer, where he stayed until 1912. From 1912 to 1918 he had an office in Nijmegen, in 1918 he stayed in Deventer again for approximately five months and from 28 August 1918 he lived and worked in Utrecht. He died there on 13 February 1937.Between 1901 and 1935 more than eighty churches and parts of churches were executed after his design. In addition, he restored twenty churches. The oeuvre can be classified into three periods: an initial phase (1901-appr. 1911), an intermediate phase (appr. 1911-appr. 1915) and his later work (appr. 1915-1935).Te Riele jr. started in the tradition of neo-Gothic, but from the very beginning, unlike the verticalism customary in that style, he aimed at placing the columns or pillars as far removed from each other as possible so that the faithful would have as unhindered a view of the main altar and pulpit as possible. For this purpose he applied the bound system without in-between pillars.All his life the architect remained faithful to churches with more than one aisle and brick vaults, although the open roof had become the rule in Roman-Catholic church architecture after the first World War. Te Riele adapted himself to the new ideas by leaving all his churches unplastered, internally as well, from approximately 1920 onwards.Especially in his late work he uses corbelled bricks in a restless manner: this restless character of his work is in sharp contrast to the restful work of Kropholler. The monumental Holy Trinity church in Oldenzaal from 1929-1930 is one of his last churches. This unprotected masterpiece distinguishes itself by the frequent application of symbolism, which had become unusual in those days.